Diseño de las condiciones operativas para el tratamiento de los vertimientos de la planta de producción de la Empresa Disaromas S. A. (2023)
The treatment of wastewater generated by the production of dyes, flavors and fragrances in the company Disaromas S.A. It is being carried out through a primary and tertiary treatment, applying chemical substances required in the process: caustic soda as an oxidant, cationic aluminum polychloride as a coagulant and anionic polymer as a flocculant obtained through jar tests carried out in water with the In order to verify the behavior of the treatment and the necessary dosage for each chemical substance, once identified, the tertiary treatment was evaluated by means of filtration with sand and gravel and likewise, by filtration with activated carbon, having turbidity values ​​greater than 140 NTU, the need to install ultrafiltration membranes was seen, which remove solids smaller than 0.03 μm and thus reduce the values ​​of chemical oxygen demand (COD) to ranges of less than 600 mg/L of O2.